The "Physics Beyond Colliders" Projects for the CERN M2 Beam - Banerjee, D.; Bernhard, J.; Brugger, M.; Charitonidis, N.; de Jesus, V.; Gatignon, L.; Gerbershagen, A.; Montbarbon, E.; Rae, B.; Rosenthal, M.; Van Dijk, M.W.U.; Veit, B.M.; et al. (Journal of physics. Conference series, 2019)
Physics Beyond Colliders is an exploratory study aimed at exploiting the full scientific potential of CERN's accelerator complex up to 2040 and its scientific infrastructure through projects complementary to the existing and possible future colliders. Within the Conventional Beam Working Group (CBWG), several projects for the M2 beam line in the CERN North Area were proposed, such as a successor for the COMPASS experiment, a muon programme for NA64 dark sector physics, and the MuonE proposal aiming at investigating the hadronic contribution to the vacuum polarisation. We present integration and beam optics studies for 100 - 160 GeV/c muon beams as well as an outlook for improvements on hadron beams, which include RFseparated options and low-energy antiproton beams and radiation studies for high intensity beams. In addition, necessary beam instrumentation upgrades for beam particle identification and momentum measurements are discussed.